ANALISIS KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK MTS NEGERI DI KOTA BIMA - Rahman, Zahra Fadhila; Suryadi, Didi; Nurjanah, Nurjanah (PHI: Jurnal Pendidikan Matematika, 2024)
Mathematical literacy skills are important to answer various problems systematically by using facts and information. This skill is important to have, especially for students. With this skill, students will be able to face today's increasingly complex developments. This research discusses the mathematical literacy skills of class VII students at one of the MTsN in Bima, West Nusa Tenggara. This research uses a descriptive qualitative approach. Data was collected through a written test with four essay questions on the material "three-dimensional shapes" especially on cubes and blocks. The questions are created based on literacy indicators of planning mathematical situations, using mathematical concepts, and interpreting mathematical results. The research results show that the indicators for planning mathematical situations and interpreting mathematical results obtained scores of 35.71 and 31.5, so they are in the low category. Meanwhile, the indicator using concepts, facts, procedures, and reasoning is quite high, 80.80. However, overall it was found that students' mathematical literacy abilities were still relatively low, so to maximize mathematics learning, efforts were needed to improve mathematical literacy abilities.